Makna Lagu Populer Batak Toba Saat Penyerahaan Ulos Hela Pada Upacara Pernikahan Batak Toba di Kota Medan - G. Siagian, Fibri; Fadlin, Fadlin; Sitopu, Sapna (Mahesa Research Center, 2025)
This Research is Entitled Analysis of the Meaning of Populer Batak Toba Songs During the Handover of Ulos Hela at Batak Toba Wedding Ceremonines in Medan City.” These three songs are always chosen to be sung before the Ulos Hela is presented to the bride and groom. To analyze the textual meaning in this study, the author uses Ferdinand de Saussure’s semiotic theory, focusing on denotative and connotative meanings. In addition, the songs Burju Marsimatua, Gabe Maho Boru, and Borhat Ma Dainang contain advice and prayers with connotative meanings that reflect the social values of the Batak Toba community. The research techniques used are fieldwork and desk work as introduced by Bruno Nettl. The author applies a qualitative method through observation, interviews, and audio-video recording. The findings of this study indicate that the Ulos Hela ceremony is a crucial highlight of the Batak Toba wedding tradition, symbolizing parental love, blessings, and the transfer of responsibility from the bride’s parents to the groom’s family.